Altered expression of AXL receptor tyrosine kinase in gastrointestinal cancers: a promising therapeutic target - Pidkovka, Nataliya; Belkhiri, Abbes (Frontiers in Oncology, 2023)
Gastrointestinal (GI) cancers that include all cancers of the digestive tract organs are generally associated with obesity, lack of exercising, smoking, poor diet, and heavy alcohol consumption. Treatment of GI cancers typically involves surgery followed by chemotherapy and/or radiation. Unfortunately, intrinsic or acquired resistance to these therapies underscore the need for more effective targeted therapies that have been proven in other malignancies. The aggressive features of GI cancers share distinct signaling pathways that are connected to each other by the overexpression and activation of AXL receptor tyrosine kinase. Several preclinical and clinical studies involving anti-AXL antibodies and small molecule AXL kinase inhibitors to test their efficacy in solid tumors, including GI cancers, have been recently carried out. Therefore, AXL may be a promising therapeutic target for overcoming the shortcomings of standard therapies in GI cancers.